Diagnostic Accuracy of Diaphragm Ultrasound in Detecting and Characterizing Patient-Ventilator Asynchronies during Noninvasive Ventilation - Vivier, Emmanuel; Haudebourg, Anne Fleur; Le Corvoisier, Philippe; Mekontso Dessap, Armand; Carteaux, Guillaume (Anesthesiology (Philadelphia), 2020)
Management of acute respiratory failure by noninvasive ventilation is often associated with asynchronies, like autotriggering or delayed cycling, incurred by leaks from the interface. These events are likely to impair patient's tolerance and to compromise noninvasive ventilation. The development of methods for easy detection and monitoring of asynchronies is therefore necessary. The authors describe two new methods to detect patient-ventilator asynchronies, based on ultrasound analysis of diaphragm excursion or thickening combined with airway pressure. The authors tested these methods in a diagnostic accuracy study. Fifteen healthy subjects were placed under noninvasive ventilation and subjected to artificially induced leaks in order to generate the main asynchronies (autotriggering or delayed cycling) at event-appropriate times of the respiratory cycle. Asynchronies were identified and characterized by conjoint assessment of ultrasound records and airway pressure waveforms; both were visualized on the ultrasound screen. The performance and accuracy of diaphragm excursion and thickening to detect each asynchrony were compared with a "control method" of flow/pressure tracings alone, and a "working standard method" combining flow, airway pressure, and diaphragm electromyography signals analyses. Ultrasound recordings were performed for the 15 volunteers, unlike electromyography recordings which could be collected in only 9 of 15 patients (60%). Autotriggering was correctly identified by continuous recording of electromyography, excursion, thickening, and flow/pressure tracings with sensitivity of 93% (95% CI, 89-97%), 94% (95% CI, 91-98%), 91% (95% CI, 87-96%), and 79% (95% CI, 75-84%), respectively. Delayed cycling was detected by electromyography, excursion, thickening, and flow/pressure tracings with sensitivity of 84% (95% CI, 77-90%), 86% (95% CI, 80-93%), 89% (95% CI, 83-94%), and 67% (95% CI, 61-73%), respectively. Ultrasound is a simple, bedside adjustable, clinical tool to detect the majority of patient-ventilator asynchronies associated with noninvasive ventilation leaks, provided that it is possible to visualize the airway pressure curve on the ultrasound machine screen. Ultrasound detection of autotriggering and delayed cycling is more accurate than isolated observation of pressure and flow tracings, and more feasible than electromyogram.